Characterization of rutting resistance of warm-modified asphalt mixtures tested in a dynamic shear rheometer - Abd Duraid M.; Ahmed Taher M.; Ahmed Thamer Y. (Journal of the Mechanical Behavior of Materials, 2023)
The current study aims to evaluate the rutting resistance of warm miox asphalt (WMA) taking into consideration the influence of production temperature. Rediset WMX, Sasobit, and Rediset LQ were used to manufacture WMAs. WMA was manufactured at 125°C (for a modified soft binder, 100/150) and 135 and 145°C (for a modified hard binder, 40/60), while the control hot mix asphalt (HMA) was manufactured at 145 and 155°C for soft and hard binder, respectively. Although WMAs manufactured using hard binder (40/60) were successfully produced at a temperature 20°C lower than that for the control HMA, its rutting performance was inferior to that of the control HMA with both Rediset LQ and Rediset WMX; while the rutting performance of the Sasobit-modified hard binder–asphalt mixture was equal to that of HMA because Sasobit increases the stiffness of binder. On the other hand, all WMAs produced at a temperature of 145°C performed better than or equal to HMA. In summary, binder grade has an important role in the dosage of additive, performance, and the reduction of the manufacturing temperature of WMA; on the other hand, WMA additives delay the degradation of rutting rate for mixes, the results also showed that WMAs have an equal performance to or better performance than that of conventional HMA.